Pengaruh Berbagai Jenis Pupuk Organik terhadap Spesies Gulma Invasif - Hutapea, Christmayaty; Syofian, Mirodi; Sudirman, Albertus (Politeknik Negeri Lampung, 2015)
The use of organic fertilizer is very instrumental to the growth and crop production, organic fertilizer can also improve soil fertility, as well as to maintain the ecosystem in the surrounding environment. In addition to providing the advantages of using organic fertilizer also has weaknesses when refining them in the process of making organic fertilizer is not good enough, potentially toxic to human health, likely to carry germs organic fertilizers, and weed seeds. This study aims to find out the weeds that dominated after the use of organic fertilizers and proving the existence of an invasive weed borne organic fertilizer. This research was carried out on open land Lampung State Polytechnic, using cow manure treatment (MS), goat manure (MK), fertilizer pome (MP), organic fertilizer factory (MB), and control (KT). This study uses a randomized block design (RAK). The observed results are weed vegetation analysis, percent weed cover, summed Dominance Ratio (SDR), and the community coefficient (C). research shows that after the application of organic fertilizers shift the dominant weed species, proving organic fertilizer bring invasive weed, and it turns organic fertilizer from the cow shed which led to the highest weed invasion.Keywords: invasive weeds, organic fertilizer, weed species shiftsPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/16